John Calvin on God’s calling: Service in the church and the world - Zeze, Willie (Stellenbosch theological journal, 2019)
Building on Martin Luther’s (1483-1546) view that the whole world could be filled with the service to God, this article is an investigation of John Calvin’s (1509-1564) assertion that every person’s occupation is a post and a station assigned to him by God. Although some people, as others did to Calvin and other reformers, may argue that the article demonstrates insensitivity to the unemployed, I have argued that restricting the word “calling” to ecclesiastical function always distorts the biblical meaning of the term. The central question in this article is simply: What can the today’s society learn from Calvin’s doctrine of occupational calling? Said differently, if Calvin and other Reformers were still alive what could they say to today’s politicians, legislators, businessmen, bankers, traders, scientists, judges and other public servants? Noting that the medieval society completely distorted the biblical truth of calling, this paper calls for a simple return to Calvin’s doctrine of vocation calling. The discussion walks from Biblical texts through the key developments in theology particularly related to how vocation was understood in the early and medieval churches that culminated in the Reformers’ view. The article concludes by offering various suppositions of what Calvin could have commended to us today.